Influence of high-intensity ultrasound application on the kinetics of sugar release from acid suspensions of artichoke (Cynara scolymus) biomass - Polachini, Tiago Carregari [UNESP]; Mulet, Antonio; Telis-Romero, Javier [UNESP]; Cárcel, Juan A. (Elsevier, 2019)
The study of sugar release kinetics is an essential step prior to developing new technologies for applying in the bioethanol industry. To this end, the kinetics of reducing and total sugar release (extraction/hydrolysis) from artichoke waste were obtained in different conditions to evaluate the solubility of free sugars from raw matter and the hydrolysis of larger chain molecules separately. Thus, experiments of extraction with water (WE), hydrolysis (HY) in acid solutions and a conventional industrial hydrolysis (IHY), which combines dissolution and hydrolysis effects, were carried out. All of the treatments were studied with ultrasound application (US) or with conventional agitation (AG). Compared to AG experiments, US application accelerated the sugar dissolution reducing 50% the time to reach the equilibrium. The decrease in the biomass concentration in the suspensions increased the US effects in HY experiments. In IHY experiments, US was also able to enhance the final yield of sugars achieving relative reducing sugar and total sugar amounts 213% and 175%, significantly higher than AG experiments. The rheological changes in the suspensions during treatments can explain the different magnitude of ultrasound effects. The acoustic field characterization and the measurement of viscosity in the acid suspensions agreed with these results.
Keywords: Fermentable sugar; Hydrolysis; Modeling; Phosphoric acid; Pretreatment